Hotel feedback system - Low, Jiang Nan (2025)
This project is a hotel feedback system application in Malaysia it is for academic purpose , focusing on Natural Language Processing (NLP) to enhance customer satisfaction and customer experience. The current system has several issues, such as requiring customers to spend a long time providing feedback, inefficient data analysis of feedback, and hindering hotel management from understanding customer emotions effectively. The purpose of this project is to develop a hotel feedback system that simplifies the feedback process for customers while enabling hotel management to easily assess their real experiences and sentiments. To address these problems, the system implements speech-to-text functionality, a categorization feature, and sentiment analysis. The method used in this project is prototyping, which allows for quick refinement of requirements and system development. The expected outcome is a system that enables users to provide feedback quickly, processes feedback data efficiently, and helps hotel management better understand customer sentiments. Additional planned features include voice recognition, feedback categorization, and sentiment analysis to interpret customer emotions. This feedback system application will undergo testing, and based on user feedback, necessary improvements—such as adding missing features or fixing functional errors—will be implemented by the developer.